RUWATAN: A RITUAL IN TRANSITION - Eddy Pursubaryanto (Gelar : Jurnal Seni Budaya, 2006)
"Where are you going, Wayang?" This question was raised by the late Umar Kayam in 1969 (Kayam 1981: 129-135) in his article as a speculative note after a Wayang Festival in Jakarta in the same year. In the article he pointed out that when the Wayang Festival started, Wayang was already very old and weak, because it had undergone a very long journey through various eras and dimensions, Its presence in its old age and at the crossroad of a changing society must have created one or two consequences. The first, Wayang was forced to arrive at new idioms. The second, it must shift emphasis, such as including new images or new identifications because at this point the time and language dimensions had so demanded. He was also predicting that the audience would change and the new audience would have different perceptions towards the characters in Wayang in general [including Wayang Kulit]. They would humanize the characters more. The audience probably would no longer use Wayang as a frame of reference in their life. Wayang would become a modern drama that avoided giving advice, but it would provide several alternatives of life. When future audiences went to a Wayang Kulit, they would no longer search for any symbolism in it. They would rather prepare to enjoy "aesthetical experiences which are full of pleasure". His writing was like a warning about the life of Indonesian Wayang if it wanted to survive and cope with the modernization era where the agricultural life was bit by bit replaced by urban life. However, Umar Kayam did not specifically look at the future Wayang Kulit in the context of ritual ceremonies, such as Ruwatan. Therefore this paper will look at some tendencies at its performance today, especially in the so-called Ruwatan Masa/(Mass Ruwatan), a new trend in Indonesia. This paper has used the data from various written resources, interviews with dalang ruwat(a dalang who has the right to perform a ruwatanceremony), and several families that participated in ruwatan. Beside that, I was involved through participatory observation as a member of the Organizing Committee of a Ruwatan Massal, and as pengrawit (gamelan player) in both regular performances and some ruwatanceremonies.